English for University Students: First Year Video Course - Тоненчук, Тетяна Василівна (My University, 2026)
This textbook contains materials necessary for organizing classroom, independent, and distance work for 1st-year students, aimed at developing listening comprehension, oral and written communication skills of an academic, social, and professional nature. The edition consists of thematic units based on 23 original English-language videos covering a wide range of everyday topics. Here, you will find tasks for listening comprehension and vocabulary training and also professional communication, such as conducting dialogues or discussions in teams. Each unit includes pre-listening discussions, video-based fact extraction, lexical tasks for explaining key terms, and detailed comprehension checks. Furthermore, the edition provides problem-solving scenarios, team debates, and role play simulations designed to foster critical thinking and effective teamwork in diverse environments – from sharing student accommodation to discussing global and local environmental challenges. The materials also include creative communication tasks, such as writing social media posts, blog snippets, and professional emails. This edition is intended for students who wish to improve their English proficiency for successful communication in academic, social, and future professional environments.
Keywords: English, university course, general English